2016
DOI: 10.3147/jsfp.51.54
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of two <i>Candidatus</i> Xenohaliotis californiensis genetic variants against three abalone species (the genus <i>Haliotis</i>)

Abstract: For half a century, Japan has practiced marine stock-enhancement programs that aim to preserve or enhance natural fisheries resources. Currently, juveniles of about 70 marine species are produced in national and prefectural hatcheries, and released annually into the wild (Fisheries Research Agency, 2015a). Because of their high market value, abalone (Haliotidae) are particularly important coastal fishery resources; 30 Japanese governmental entities (city or prefectural governments) currently produce and releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Rickettsial infections in Haliotis diversicolor supertexta ( 17 ), caused similar symptoms, but symptoms and mortality only occurred at water temperatures of 30°C. ( 18 ) also showed that at least 2 genetic variants show a different host specificity. Vibrio parahaemolyticus has also been isolated from H. diversicolor supertexta in Taiwan showing signs of withering syndrome ( 19 , 20 ).…”
Section: Bacteriamentioning
confidence: 98%
“…Rickettsial infections in Haliotis diversicolor supertexta ( 17 ), caused similar symptoms, but symptoms and mortality only occurred at water temperatures of 30°C. ( 18 ) also showed that at least 2 genetic variants show a different host specificity. Vibrio parahaemolyticus has also been isolated from H. diversicolor supertexta in Taiwan showing signs of withering syndrome ( 19 , 20 ).…”
Section: Bacteriamentioning
confidence: 98%
“…While other abalone species like H. fulgens and H. corrugata are more resistant (Álvarez Tinajero et al, 2002; Moore et al, 2009; Cruz‐Flores et al, 2016). Cohabitation studies of infect abalone species by two genetic variants of C Xc in Japan showed that these variants have different host specificity (Nishioka et al, 2016). This might also be the case for other RLOs capable of infecting different mollusc species, where the RLO could act as harmless symbiont in one species and be highly pathogenic for other species.…”
Section: Rlos As Mortality‐causing Agentsmentioning
confidence: 99%
“…The first Rickettsiales‐like organism from a marine mollusc was described in the soft shell clam Mya arenaria in 1977 by Harshbarger and Chang, (1977); since then, over 60 species of marine bivalve mollusc, one species of freshwater clam ( Rangia flexuosa ), one species of fresh water mussel ( Dreissena spp.) and at least ten gastropod species have been reported to harbour these organisms (Nishioka et al, 2016 and see Table 1 for more references). Rickettsiales‐like organisms (RLOs) are small intracellular prokaryotes that are generally found within intracytoplasmic vacuoles (IVs) in numerous tissues of bivalve and gastropod molluscs of fishery and aquaculture importance.…”
Section: Introductionmentioning
confidence: 99%